2011
DOI: 10.1016/j.heares.2010.10.020
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of the role of metabotropic glutamate receptors in the afferent regulation of chick cochlear nucleus neurons

Abstract: Cochlea removal results in the death of approximately 20-30% of neurons in the chick nucleus magnocellularis (NM). One early event in NM neuronal degradation is the disruption of their ribosomes. This can be visualized in the first few hours following cochlea removal using Y10B, an antibody that recognizes ribosomal RNA. Previous studies using a brain slice preparation suggest that maintenance of ribosomal integrity in NM neurons requires metabotropic glutamate receptor (mGluR) activation. Isolating the brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This activity-dependent regulation of protein synthesis does not involve ionotropic glutamate receptors (Hyson, 1997), but rather relies on activity of mGluRs (Hyson, 1998). Specifically, group I and II mGluRs are required to maintain protein synthesis in NM neurons, because blocking either group I or II mGluRs eliminates activity-dependent regulation of ribosomes in vitro (Nicholas and Hyson, 2004) as well as in vivo (Carzoli and Hyson, 2011). These studies demonstrate the regulatory roles of mGluRs in Ca 2+ signaling and protein synthesis, suggesting potential neuroprotective effects of mGluRs under abnormal hearing conditions.…”
Section: Anatomy and Physiology Of Mglurs In Avian Lower Auditory Bramentioning
confidence: 99%
“…This activity-dependent regulation of protein synthesis does not involve ionotropic glutamate receptors (Hyson, 1997), but rather relies on activity of mGluRs (Hyson, 1998). Specifically, group I and II mGluRs are required to maintain protein synthesis in NM neurons, because blocking either group I or II mGluRs eliminates activity-dependent regulation of ribosomes in vitro (Nicholas and Hyson, 2004) as well as in vivo (Carzoli and Hyson, 2011). These studies demonstrate the regulatory roles of mGluRs in Ca 2+ signaling and protein synthesis, suggesting potential neuroprotective effects of mGluRs under abnormal hearing conditions.…”
Section: Anatomy and Physiology Of Mglurs In Avian Lower Auditory Bramentioning
confidence: 99%
“…On the other hand, blockade of mGluRs does prevent this activity-dependent regulation [21] , [23] . The importance of mGluR activation has also been confirmed in vivo where it has been shown that blockade of mGluRs reduces ribosomal antigenicity and produces NM neuronal death even with an intact cochlea [25] . The current set of experiments demonstrate that providing mGluR activation to NM neurons is sufficient, at least in the early stages that follow deafferentation, to maintain healthy ribosomes.…”
Section: Discussionmentioning
confidence: 89%
“…The Y10B antiserum was raised from a clone originally developed by J. Steitz and subsequently supplied to our laboratory by E. Rubel. This antibody is an established marker of changes in ribosomes [26] , and has been used extensively as an indicator of the early changes resulting from deafferentation (e.g., [15] , [17] , [18] , [25] , [27] ). Changes in antigenicity appear to match changes in overall protein synthesis and a deafferentation-induced reduction in Y10B labeling has been confirmed at the EM level [15] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have shown that this activity-dependent regulation of protein synthesis relies on activity of mGluRs [124,125], but not involve iGluRs [126]. Specifically, group I and II mGluRs are required to maintain protein synthesis in NM neurons, because blocking either group I or II mGluRs eliminates activity-dependent regulation of ribosomes in vitro [127,128] as well as in vivo [129]. Together, these studies demonstrate the regulatory roles of mGluRs in Ca 2+ signaling and protein synthesis, suggesting potential neuroprotective effects of mGluRs under both normal and abnormal hearing conditions.…”
Section: Mglurs In Avian Auditory Brainstemmentioning
confidence: 99%